Research Progress of Vertical Channel Thin Film Transistor Device - Benxiao Sun; Huixue Huang; Pan Wen; Meng Xu; Cong Peng; Longlong Chen; Xifeng Li; Jianhua Zhang (Sensors, 2023)
Thin film transistors (TFTs) as the core devices for displays, are widely used in various fields including ultra-high-resolution displays, flexible displays, wearable electronic skins and memory devices, especially in terms of sensors. TFTs have now started to move towards miniaturization. Similarly to MOSFETs problem, traditional planar structure TFTs have difficulty in reducing the channel’s length sub-1μm under the existing photolithography technology. Vertical channel thin film transistors (V-TFTs) are proposed. It is an effective solution to overcome the miniaturization limit of traditional planar TFTs. So, we summarize the different aspects of VTFTs. Firstly, this paper introduces the structure types, key parameters, and the impact of different preparation methods in devices of V-TFTs. Secondly, an overview of the research progress of V-TFTs’ active layer materials in recent years, the characteristics of V-TFTs and their application in examples has proved the enormous application potential of V-TFT in sensing. Finally, in addition to the advantages of V-TFTs, the current technical challenge and their potential solutions are put forward, and the future development trend of this new structure of V-TFTs is proposed.